Functional performance in self‐care and mobility after selective dorsal rhizotomy: a 10‐year practice‐based follow‐up study. (30th October 2014) - Josenby, Annika Lundkvist; Wagner, Philippe; Jarnlo, Gun‐Britt; Westbom, Lena; Nordmark, Eva
<x xml:space="preserve">Abstract</x> Aim To explore changes in performance in daily activities (self‐care and mobility) 10 years after selective dorsal rhizotomy (SDR). Method Twenty‐four children with bilateral spastic cerebral palsy were followed; the median age at SDR was 4 years 1 month (range 2y 5mo–6y 4mo) and at 10‐year follow‐up was 14 years 6 months (range 12y 3mo–16y 9mo). The preoperative Gross Motor Function Classification System (GMFCS) levels were: I (n=1), II (n=7), III (n=4), IV (n=11), and V (n=1). The Pediatric Evaluation of Disability Inventory (PEDI) was used to assess performance in functional skills, caregiver assistance, and frequency of modifications and adaptive equipment (MAE) in self‐care and mobility domains. Changes were analysed in relation to preoperative GMFCS levels, PEDI scores, and age at operation. Results All scores improved significantly (p<0.01) during the first 5 years in patients assigned to GMFCS levels I–III and IV–V. Between 5 years and 10 years, changes were seen in patients grouped in GMFCS levels I–III in the functional skills, mobility (p=0.04), caregiver assistance self‐care (p=0.03), and caregiver assistance mobility (p=0.03) domains. Those grouped in GMFCS levels IV–V showed small changes between 5 years and 10 years after surgery. Changes were dependent on the preoperative GMFCS levels in all domains; caregiver assistance, self‐care and mobility changes were dependent on preoperative values. The use of MAE increased in participants in GMFCS levels IV–V. Interpretation Children who underwent SDR and physiotherapy improved in functional performance in self‐care and mobility and were more independent 10 years postoperatively.